Retardation of development of renal failure - Idasiak-Piechocka, Ilona; Czekalski, Stanisław (Przewodnik Lekarza/Guide for GPs, 2007)
The only possibility to reduce the constantly increasing number of patients qualified for renal replacement therapy is effective prevention of progression of chronic kidney disease (CKD) toward end-stage renal failure (ESRF). Apart from early diagnosis and treatment of primary factors causing kidney damage, multifactorial intervention is required consisting principally of: optimal glycaemic control in patients with diabetes and in all patients with CKD: good control of blood pressure, using drugs with nephroprotective properties, control of lipid disturbances, recommendation of adequate diet, treatment of obesity, disturbances of calcium-phosphate metabolism, anaemia, chronic inflammation and all other risk factors of atherosclerosis.